Alcohol‐induced Wnt signaling inhibition during bone fracture healing is normalized by intermittent parathyroid hormone treatment. Issue 2 (7th May 2020) - Kapania, Esha M.; Reif, Taylor J.; Tsumura, Aaron; Eby, Jonathan M.; Callaci, John J.
Abstract: Nearly half of orthopaedic trauma patients are intoxicated at the time of injury, and excess alcohol consumption increases the risk for fracture nonunion. Previous studies show alcohol disrupts fracture associated Wnt signaling required for normal bone fracture repair. Intermittent parathyroid hormone (PTH) promotes bone growth through canonical Wnt signaling, however, no studies have investigated the effect of PTH on alcohol‐inhibited bone fracture repair. Male C57BL/6 mice received two‐3 day alcohol binges separated by 4 days before receiving a mid‐shaft tibia fracture. Postoperatively, mice received PTH daily until euthanasia. Wnt/β‐catenin signaling was analyzed at 9 days post‐fracture. As previously observed, acute alcohol exposure resulted in a >2‐fold decrease in total and the active form of β‐catenin and a 2‐fold increase in inactive β‐catenin within the fracture callus. Intermittent PTH abrogated the effect of alcohol on β‐catenin within the fracture callus. Upstream of β‐catenin, alcohol‐treated animals had a 2‐fold decrease in total LRP6, the Wnt co‐receptor, which was restored with PTH treatment. Alcohol nor PTH had any significant effect on GSK‐3β. These data show that intermittent PTH following a tibia fracture restores normal expression of Wnt signaling proteins within the fracture callus of alcohol‐treated mice.